Improving Adolescent Mental Health Development through Therapeutic Group Therapy in Saint Beatrix Orphanage, Sidoarjo - Anindya Arum Cempaka; Putu Indraswari Aryanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Adolescents who live at an orphanage may be at risk of mental disorders among adolescents. As adolescent orphans usually have bad memories, therapeutic groups are alternatives to overcome this issue. A civic engagement program was conducted to tackle development issues in adolescents as it performed a therapeutic approach with their peers. This program involved twenty-one female adolescents in Saint Beatrix orphanage Sidoarjo. They took a pre-test, which indicated a low level of knowledge about adolescent development. Group therapy was conducted in seven sessions, each of which took an hour. In the evaluation stage, questionnaires were distributed to test the adolescents’ knowledge about adolescent development. After conducting the therapeutic group therapy, it showed that adolescents’ knowledge about the development stages and their challenges improved. Based on the result of the Wilcoxon Sign Rank Test, it's known that p-value = 0,000 with (ɑ<0.05), which means therapeutic group therapy may enhance knowledge about adolescent development stages to promote a healthy lifestyle in adolescents